Mastering 1-2-3 - Jorgensen, Carolyn; Guy, Aisling (San Francisco : SYBEX, 1988)
Lotus 1-2-3, as the name implies, id three different programs combined into one integrated package: spreadsheet, database, and graphics. This book is for everyone who uses Lotus 1-2-3 or wants to use it.
"With fast track speed notes"--Cover.
"The SYBEX Lotus 1-2-3 command chart" inserted at end.
Includes index.
II 15/01/2019
Loans
Keywords: Business; Electronic spreadsheets